Examining the sustainability of Screening for Distress, the sixth vital sign, in two outpatient oncology clinics: A mixed‐methods study. Issue 1 (10th February 2017) - Groff, Shannon; Holroyd‐Leduc, Jayna; White, Deborah; Bultz, Barry D.
Abstract: Background: Research indicates that cancer patients experience significant multifactorial distress during their journey. To address this, cancer centers are implementing Screening for Distress programs; however, little is known about the sustainability of these programs. This study sought to examine the sustainability of a Screening for Distress program in 2 cancer clinics 6 months post implementation. Methods: A mixed‐methods cross‐sectional design was utilized. To determine if screening rates, screening conversations and appropriate interventions occurred and the charts of 184 consecutive patients attending the head and neck or neuro‐oncology clinics over a 3 week period were reviewed. To examine the barriers and facilitators of sustainability, 16 semi‐structured interviews with administrators, physicians, and nurses were conducted. Results: Of the 184 charts reviewed, 163 (88.6%) had completed screening tools. Of these 163, 130 (79.8%) indicated that a conversation occurred with the patient about the identified distress as reported on the screening tool. Of the 89 (54.6%) charts where the need for an intervention was indicated, 68 (76.4%) had an intervention documented. Six oncologists, 7 nurses, and 3 administrators were interviewed, and 5 themes which influenced the sustainability of the program emerged: (1) attitudes, knowledge, and beliefs about the program; (2) implementation approach; (3) outcome expectancy of providers; (4) integration with existing practices; and (5) external factors. Conclusions: This study suggests that Screening for Distress was largely sustained, possibly due to positive attitudes and outcome expectancy. However, sustainability may be enhanced by formally integrating screening with existing practices, addressing potential knowledge gaps, and ensuring engagement with all stakeholder groups.